2013
DOI: 10.1109/tns.2012.2235464
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects on Silica-Based Optical Fibers: Recent Advances and Future Challenges

Abstract: International audienceIn this review paper, we present radiation effects on silica-based optical fibers. We first describe the mechanisms inducing microscopic and macroscopic changes under irradiation: radiation-induced attenuation, radiation-induced emission and compaction. We then discuss the influence of various parameters related to the optical fiber, to the harsh environments and to the fiber-based applications on the amplitudes and kinetics of these changes. Then, we focus on advances obtained over the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
228
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 418 publications
(249 citation statements)
references
References 168 publications
6
228
0
6
Order By: Relevance
“…However, their use in harsh environments associated with ionizing radiation is negative for the optical performance due to the generation of point defects that introduce localized levels within the forbidden band gap thus causing radiation induced absorption (RIA). The radiation effects in silica have been, therefore, the object of intensive studies over the last decades [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their use in harsh environments associated with ionizing radiation is negative for the optical performance due to the generation of point defects that introduce localized levels within the forbidden band gap thus causing radiation induced absorption (RIA). The radiation effects in silica have been, therefore, the object of intensive studies over the last decades [1].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that pure silica core (PSC) and F-doped fibers exhibit low RIA in the UV-Visible spectral domain for high irradiation doses [1]; they are, for this reason, of particular interest for the design of radiation hardened distributed fiber sensors for nuclear industry.…”
Section: Introductionmentioning
confidence: 99%
“…For this aim, fiber-based sensors like those based on fiber Bragg gratings (FBGs) present several advantages, like a faster time response than thermocouples (lower than 1 s) and a high radiation tolerance, as investigated by previous studies [2]. However, radiation is also known to alter the fiber transmission properties as well as the FBG properties [2,3]. Furthermore, the amplitudes and kinetics of these changes are dependent on temperature, as this extrinsic parameter governs the stability of the radiation induced point defects in the silica-based glass at the origin of these macroscopic changes [2,3].…”
mentioning
confidence: 99%
“…However, radiation is also known to alter the fiber transmission properties as well as the FBG properties [2,3]. Furthermore, the amplitudes and kinetics of these changes are dependent on temperature, as this extrinsic parameter governs the stability of the radiation induced point defects in the silica-based glass at the origin of these macroscopic changes [2,3]. Another important point, as clearly shown in a paper by Henschel et al [4], is that the radiation sensitivity of a fiber and of an FBG written in this fiber are not directly correlated but will depend on many other parameters like the FBGs' writing technique and conditions as well as the possible hydrogen-loading before inscription [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation